Peningkatan Kepuasan Pasien dengan Nursing Rounds - Cencen Hendra Setiawan; Ati Surya Mediawati; Kurniawan Yudianto (Jurnal Keperawatan Silampari, 2023)
This study aims to determine how implementing nursing rounds affects patient satisfaction. The method used is a literature review using an identified electronic database from Pubmed, EBSCOhost, and Google Scholar. Search using keywords, namely nurse, Nursing rounds, hourly rounds, and patient satisfaction. The search results included seven articles filtered from 2020 – 2022, which resulted in nursing rounds increasing patient satisfaction, patient safety, and preventing extravasation of infusion fluids. Nursing rounds can also be carried out with other professions. As a result, nursing rounds carried out by nurses in a measurable and planned manner can increase patient satisfaction. In conclusion, nurses can increase patient satisfaction while hospitalized by implementing nursing bands carried out regularly and structured for their managed patients. Besides that, the benefits of nursing rounds can also increase patient satisfaction and prevent the extravasation of infusion fluids. Keywords: Patient Satisfaction, Nurses, Nursing Rounds, Hourly Rounds